SHOPFinder application - Buareng, Muhamad Atiq Fahim; Alkadzlie, Al Zikri; Abdul Rasit, Nurul Shafika Norkhatijah; Paulus, Vassylysa Eirlys; Mohamad Musa, Nurafiqah (Universiti Teknologi MARA, Kedah, 2023)
SHOPFinder is a mobile application created to improve the travel experience by giving customers a convenient and customized buying experience. The app provides a wide choice of travel-related goods, including necessities, apparel, accessories, and mementos, all of which have been carefully chosen to meet the needs and preferences of travellers. Innovative features including augmented reality product visualization, geo-location-based suggestions, virtual personal shopping assistants, and social shopping integration are included. Users of the app may quickly browse, choose, and buy things while also taking advantage of special deals and discounts. By exhibiting distinctive goods from various locations, the app promoteslocal business support, community participation, and crosscultural interaction. By emphasizing products with ethical and ecologically conscious sourcing, it encourages sustainability and ethical buying habits.